أثر جائحة كوفيد – 19 المستجد على قطاع السياحة العالمي - بن ميلود, عبد القادر; زروخي, فيروز (جامعة الوادي University of Eloued, 2021)
تتطور وتنمو السياحة يوما بعد يوما باعتبارها نشاطا عالميا عملاقا إستحوذت على 10.4 % من الناتج المحلي الاجمالي العالمي و10 % من القوى العاملة العالمية، وتهدف هذه الورقة البحثية إلى رصد وإكتشاف المخاطر التي يتحملها قطاع السياحة جراء تبعات انتشار وباء كوفيد 19 المستجد، وما يتصف به من هشاشة والتكاليف التي سيتحملها، سيعرف قطاع السياحة العالمي مستقبلا صدمات قوية ومؤثرة تصل إرتداداته بشكل عنيف ومدمر في الدول التي تعتمد على السياحة كمصدر أساسي للدخل. كما أن سياسة الإغلاق التي إعتمدتها بعض البلدان لمنع تفشي الوباء أدى إلى تعطيل سلسلة القيمة العالمية والمليارات من الدولارات مع إنهيار إقتصادي الذي تسبب في إرتفاع قياسي في معدلات البطالة خصوصا في البلدان التي تشهد حالات كبيرة من إنتشار هذا الفيروس .وتهدف هذه الورقة البحثية إلى إقتراح بعض الحلول الممكنة خصوصا للبلدان التي تعتمد على السياحة كمورد أساسي للدخل للتكيف معها مستقبلا ولمصممي الاستراتيجيات السياحية و الحكومات والقطاعات الإقتصادية الأخرى الغير مرتبطة بها التي أدت إلى شلل في سلسة القيمة العالمية . Tourism is developing and growing day by day as a gigantic global activity that has acquired 10.4% of the global GDP and 10% of the global workforce, and this research paper aims to monitor and discover the risks that the tourism sector bears as a result of the consequences of the spread of the emerging Covid 19 epidemic and its characteristics The fragility and costs that it will bear, the global tourism sector will know in the future strong and influential shocks, and its repercussions will reach in a violent and destructive manner in countries that depend on tourism as a main source of income. Also, the closure policy adopted by some countries to prevent the outbreak of the epidemic led to disruption of the global value chain and billions of dollars with an economic collapse that caused a record high in unemployment rates, especially in countries that witness large cases of the spread of this virus. This research paper aims to suggest some possible solutions, especially for countries that depend on tourism as a main source of income to adapt to it in the future, and for tourism strategists, governments and other economic sectors that are not related to them that have led to paralysis in the global value chain
The impact of the emerging Covid 19 pandemic on the global tourism sector
مقال
Keywords: فيروس كوفيد 19، قطاع السياحة، صناعة السياحة